2020
DOI: 10.1002/anie.202010497
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Chemical Role of the Pyroclastic Materials on the State of Conservation of Mural Paintings from Pompeii

Abstract: ]. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…This is also guaranteed due to the previously assessed influence of groundwater in this archeological site. 4 , 25 …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is also guaranteed due to the previously assessed influence of groundwater in this archeological site. 4 , 25 …”
Section: Results and Discussionmentioning
confidence: 99%
“…This is also guaranteed due to the previously assessed influence of groundwater in this archeological site. 4,25 Whereas certain authors concluded that this phenomenon takes place under abiotic conditions, others held that microorganisms control Mn precipitation 35 (biomineralization of Mn).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, fossil pigments are indeed biologically originated but preserved in fossils for millions of years, acting as evolutionary evidence [ 48 , 49 , 50 , 51 , 52 , 53 ]. In rare cases, fossil pigments can be of synthetic origin [ 54 ]. Mineral pigments are inorganic insoluble pigments used in artistic, cosmetic, archeological, and evolutionary studies [ 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Classification Of Pigmentsmentioning
confidence: 99%